Ethical dilemmas: Experiences of secondary school teachers in Addis Ababa city, Ethiopia - Tigist Wuhib Tsega (College of education, Bahir Dar University, 2024)
Being a teacher involves multi-layered ethical challenges and decisions. The purpose of this research was to explore the ethical dilemmas faced by secondary school teachers in Addis Ababa, Ethiopia. In addition, the study aimed to explore the ways and approaches to resolving ethical dilemmas. A phenomenological qualitative research approach served as the guiding methodology. Eight participants were involved in the semi-structured in-depth interviews. Data were analyzed by exploring potential themes and sub-themes using thematic analysis. The major ethical dilemmas that emerged from the data include (a) not being governed by schools' rules and regulations (disrespect and dis-rule), (b) not being honest in the position they have, (c) lack of acceptance and recognition among the school community, and (d) being indecisive due to deep personal challenges of students and political interference. The major approaches utilized in addressing ethical challenges were (a) respecting the code of conduct of students' discipline, (b) open discussion and confrontation, (c) understanding causal factors, and (d) being ethical. The need for professional development plans and training based on guiding books have been suggested as means of action in preparing secondary school teachers to deal with ethical challenges and to help them be good at decision-making.